Ultrasensitive thrombin sensing platform based on three-way junction initiated dual signal amplification - Hongxiu Yang; Lixuan Hou; Chunjing Liu; Wei Liu; Lihua Li (Journal of Analytical Science and Technology, 2022)
Abstract The sensitive and precise quantitative determination of thrombin is important for both fundamental research and clinical diagnostics of hypoxic ischemic encephalopathy because it is a key biological molecule in hemostasis and hemolysis. Herein, we depict a sensitive and label-free thrombin detection approach by taking the advantages of aptamer’s superior capability to bind with thrombin and the high efficiency of three-way junction initiated dual signal recycle. In this method, a capture probe which is inserted with an aptamer sequence is designed to specifically identify thrombin molecule and facilitate the signal amplification. Based on the DNA polymerase and endonuclease Nb.BbvCI-assisted chain extension, a large amount of single-strand DNA sequences that can fold into G-quadruplex are produced to specifically recognize commercial fluorescent dye thioflavin T for signal generation. Consequently, the approach exhibits a high detection sensitivity with the limit of detection as low as 768 fM, holding a great promise for detection of thrombin and disease diagnosis in the clinic.